RETROSPECTIVE ANALYSIS OF MYOCARDIAL RUPTURE CASES IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - L. E. Rudakova; F. K. Rakhmatullov; L. A. Bondarenko; M. F. Fatkabrarov; A. M. Fatkabrarova (Российский кардиологический журнал)
The paper focuses on myocardial rupture in acute myocardial infarction, based on the annual reports of Penza City cardiology service (2003-2008) and retrospective medical history analysis of 61 patients, who died in cardiology and therapy departments of city hospitals due to acute myocardial infarction and myocardial rupture. The prevalence, morphological and clinical features of myocardial rupture in acute myocardial infarction are described.